Detection and assessment of Dimethyl phthalate and Antimony migration in different drinking water samples under various storage temperatures in Al-Diwaniyah city - Abd, Abbas Rahman; Muhsin, Fulath Abdul-Redah (Adolescência e Saúde, 2026)
The widespread use of plastic-packaged drinking water has raised increasing concerns regarding the migration of hazardous chemical contaminants under high temperature conditions. this experimental study aimed to assess the effect of storage temperatures on the migration of dimethyl phthalate (DMP) and antimony (Sb) into drinking water packaged in polyethylene terephthalate(PET) ,polypropylene (PP) and high density polyethylene (HDPE) containers in AL-Diwaniyah city,Iraq. A total of 36 drinking water samples were collected from local markets, nine of these samples were transferred into clean sterilized glass bottles and sent directly to the laboratory to investigates about presence of DMP and Sb at markets temperatures (18°C). While, 27 samples were exposed to three temperature conditions (25 °C, 35 °C, and 45 °C) ,also sent to the laboratory with the aim of assessing the effect of different storage temperatures on the migration of these contaminants. DMP concentrations are determined using high-performance liquid chromatography (HPLC).while, Sb concentrations were determined by atomic absorption spectroscopy (AAS).The findings showed a highly significant increase (P ≤ 0.001) in both DMP and Sb concentration with increasing temperatures across all plastic types. the concentration of DMP in PET plastic reached to (15.618±0.373 µg/L)at 45°C,in PP plastic reached to (16.922±1.048 µg/L) at 45°C.while, in HDPE plastic reached to the highest recorded level (17.319±0.391µg/L) at 45°C. the concentration of Sb in PET plastic reached to (17.133 µg/L) at 45°C,in PP plastic reached to (42.800±0.721µg/L) at 45°C. While, HDPE, exhibited the highest overall migration at elevated temperatures, reached to (50.267±0.306 µg/L) at 45°C.this study concluded that elevated environmental temperatures significantly increase the leaching of organic and inorganic pollutants from plastic packaging into drinking water, potentially exceeding global conservation standards and causing public health risks. these findings emphasize the urgent need for stricter storage policies, improved packaging materials, and enhanced public awareness of safe bottled water storage in hot climates .